Gastrointestinal bleeding as a result of entero-iliac fistula due to intestinal foreign body - Valiyeva, Sayali (Ann Med Surg (Lond), 2020)
Ingested toothpicks are a relatively rare event, but they may cause serious gut injuries and can be listed among rare causes of perforation, peritonitis, sepsis or death. Unless the foreign bodies were intentionally swallowed, many patients who ingested them fail to remember the event and they do not refer it during the medical history collection; this makes diagnosis problematic. In this work, a case of perforation of the sigmoid colon is described, caused by a toothpick ingestion. The patient had to be surgically treated because of a complication: the formation of an entero-iliac fistula with subsequent development of a pseudoaneurysm of the right external iliac artery. Vascular perforation due to toothpick ingestion has rarely been reported. In similar cases, it could be difficult to establishing the correct diagnosis because of the low sensitivity and accuracy rates of diagnostic investigations. The ingestion of foreign bodies should be kept in mind as an important differential diagnosis in patients with acute abdomen or chronic abdominal pain of unknown origin.